Long term supplementation of Lactobacillus plantarum PS128 attenuated high-intensity exercise induced acute-phase inflammation in triathletes - Huang, H.-Y.; Tsao, S.-P. (Current Developments in Nutrition, 2020)
Objectives: A triathlon, which consists of swimming, bicycling, and running, is a high-intensity and long-term form of exercise that can cause injuries such as muscular damage, inflammation, oxidative stress, and energy imbalance. Previous studies indicated that Lactobacillus supplementation could improve oxidative stress and inflammatory responses. We investigate the effects of Lactobacillus plantarum PS128 supplementation on triathletes for shorten the acute inflammatory phase.